A novel method for hyoid suspension using a magnetic device in beagles: A preliminary study - Zong-Wu Yao; Nadiya Nuerbolati; Pei-Xi Li; Xuan-Yu Qi; Rui-Zhe Wang; Jia-Hao Zhang; Lin-Biao Xiang; Jia-Wei Yu; Ai-Hua Shi; Lu Ren; Lei Zhang; Ying-Min Yao; et al. (Scientific Reports)
Abstract Current methods for hyoid suspension in the treatment of upper airway (UA) collapse have some shortcomings. The application of a magnetic force to displace the hyoid bone has been reported to improve UA geometry in a human cadaver model. Therefore, this study aimed to develop a novel magnetic device for improving UA geometry and to verify its safety and feasibility in beagle canines. Ten healthy beagle canines were assigned to receive hyoid suspension using a newly designed magnetic device. An improvement in UA geometry was evaluated by laryngeal inspection and X-ray imaging before and after hyoid suspension. The magnitude of the magnetic force and the distance between the internal and external magnets were measured before and after the improvement in UA geometry. The barking and swallowing functions of all dogs were also observed 1 week after surgery. The procedure was successful, and all dogs survived after surgery. UA geometry significantly improved after hyoid suspension using this magnetic device in all canines. The distance between the hyoid bone and the cervical vertebrae significantly increased after hyoid suspension. The distance between the internal magnet and external magnet was 2.5 ± 0.2 cm, while the magnetic force between the two magnets was 3.5 ± 0.4 N when UA geometry had improved. The barking and swallowing functions of all canines did not change after surgery. This newly designed magnetic device is reliable and effective in improving UA geometry in beagle dogs.